FOSTERING EMPLOYEES’ INTENTION TO STAY IN THE HOTEL INDUSTRY IN NIGERIA: THE IMPACT OF WORK MOTIVATION, ORGANIZATIONAL SUPPORT, AND HAPPINESS AT WORK - Ononye, Uzoma Heman (Jurnal Manajemen dan Kewirausahaan, 2025)
The hotel industry in Nigeria is experiencing a low employee retention rate, which may be exacerbated by rising competition from both established and new entrants to the industry, resulting in a struggle for available talent. The study examined how employees’ intention to stay (ITS) in hotel employment is fostered, focusing on the direct effect of work motivation and the indirect effects of organizational support and happiness at work. The study obtained cross-sectional data through a structured questionnaire administered to 178 customer-contact staff in hotels located in Asaba, Delta State, Nigeria. The partial least squares method was used for data analysis. The study found that both intrinsic and extrinsic motivation positively influenced ITS, with extrinsic motivation having a more pronounced effect on the outcome variable. Furthermore, organizational support and happiness at work partially mediated these positive influences, acting both separately and in sequence. The study concluded that while enhancing both work motivation dimensions directly improves ITS in Nigerian hotels, fostering a supportive and happy workplace can provide a reinforcing context to complement this improvement. The study discussed the practical implications for promoting ITS within the hotel industry.